Transformasi Pengentasan Kemiskinan Keluarga Fakir Miskin Penerima Program Keluarga Harapan (Studi di Desa Wonodadi Kecamatan Gadingrejo Kabupaten Pringsewu) - Junaidi, Junaidi; Purboyo, Muhammad Guntur; Amriwa, Azis (Administratio, 2021)
Program Keluarga Harapan (PKH) exists as a government program that provides conditional assistance to families belonging to the poor. Since its birth in 2007, PKH has changed along with the dynamics of society. To see these developments, and how the reality of recipients belonging to poor families receiving PKH benefits is something that needs to be known scientifically. Therefore, in this study, structural functionalism is used as an analytical tool for solving theoretical problems that arise from the existence of PKH. This study uses a qualitative method with case study analysis. In addition, this study is also supported by quantitative data in the form of secondary data. This research was conducted in Wonodadi Village, Gadingrejo District, Pringsewu Regency. With this method and the field of study to be studied, this study will produce the reality of PKH beneficiary families in their social life. The aim is to find out the condition of the community comprehensively, and it is useful to provide an overview and solutions that can be offered if the assistance does not succeed significantly. From the description found, PKH Beneficiary Families (KPM PKH) have not been able to be socially independent so they tend to look dependent.